Insecticidal efficacy of Chrysanthemum cinerariaefolium Seed Oil Against Cowpea Beetle and Its Impact on the Physicochemical and Technological Characteristics of Cowpea during Storage - Seham, Y. Gebreil; Sanaa, M. Mahgoub; Mawaheb, M. Zewar; Doaa, M. Gharib (Food Technology Research Journal)
Essential oil from Chrysanthemum cinerariaefolium seeds was extracted using a soxhlet extractor for 48 hours. The oil extract's insecticidal activity against adult cowpea beetles (Callosobruchus maculatus) was investigated at concentrations of 0.01, 0.03, 0.05, 0.1, and 0.18%. Data showed that seed extract caused significant insect mortality. The mortality percentage reaches 100% after three days of exposure at a concentration of 0.18% of the extract. Data was carried out on the effect of oil on some biological aspects of C. maculatus (total number of eggs, egg hatchability, adult emergence, and reduction percentage). The LC95 (0.4%) of Chrysanthemum oil was assessed for physicochemical and technological characteristics during a storage period of 12 weeks. The treated cowpea seeds showed an unchanged chemical composition at zero time. During storage periods, the tested treatment reduces the rate of decreasing length, width, lightness, and redness. The 1000-weight seed and yellowness value were higher in treated seeds than in untreated seeds. A decrease in the cooking time and total soluble solids of treated cowpea seeds during storage. While the water uptake ratio, hydration and swelling capacity, the moisture, protein content and in vitro protein digestibility of treated cowpea seeds were higher than those of the untreated at the end of storage, the treated cowpea seed samples were acceptable in all tests of sensory acceptability. This study recommended using Chrysanthemum seed oil (0.4%) for management of the C. maculatus population while maintaining the nutritional and technological quality of cowpea seeds during storage and avoiding risks from chemical insecticides.